The Grey Areas: Notary Liability and Intern Supervision in Indonesian Legal Practice - Nabila, Selma; Widhiyanti , Hanif Nur; Wisnuwardhani, Diah Aju (Invest Journal of Sharia & Economic Law, 2024)
This study examines the legal responsibilities and protections for notaries supervising interns in Indonesia, focusing on potential violations and the challenges posed by the differing legal statuses of interns and permanent staff. Employing a normative juridical method with statute and conceptual approaches, this research analyzes Article 16A of Law Number 2 of 2014 on Notary Position, which mandates supervisory duties for notaries but lacks clarity on liability boundaries. The absence of detailed regulations exposes notaries to legal and reputational risks as they may face litigation for interns' misconduct. Inconsistent internship practices across notarial offices further complicates this issue. This study highlights practical challenges, such as managing interns' access to sensitive client information and maintaining confidentiality. These challenges are exacerbated by interns' status as trainees rather than employees, which limits the supervising notary's control and accountability. These findings underscore the need for explicit guidelines to protect notaries from unintended liability while ensuring effective mentorship. Recommendations include implementing specific regulations on supervision, mandatory ethics training for interns, and limited access to protocols. Collaboration with professional associations to establish best practices and maintain a balance between legal responsibilities and training quality is advised. This study contributes to the understanding of professional responsibility in the notarial profession and highlights the importance of clear legal frameworks to support supervisors and maintain public trust.